Dispute settlement reports 1997 (Cambridge university press, 2000)
The Dispute Settlement Reports of the World Trade Organization (WTO) include Panel and Appellate Body reports, as well as arbitration awards, in disputes concerning the rights and obligations of WTO members. These are the authorized paginated reports in English: as such, they are an essential addition to the library of all practising and academic trade lawyers, and an important reference for students taking courses in international economic or trade law. Cases included concern: restrictions on imports of cotton and man-made fibre underwear; desiccated coconut; imports of woven wool shirts and blouses from India; and periodicals.